MOBILE TECHNOLOGIES IN EDUCATION (Revista Contexto & Educação, 2021)
The objective of the article is to analyze the implementation process of the project 'Mobile Technologies: insertion of tablets in education' in two public schools in the municipal education network of Salvador, Bahia. We used the qualitative approach, the descriptive method, the field research methodology and as an observation technique, the interview. Eight individuals collaborated as research subjects and the data were evaluated under the guidance of content analysis. As a result, three axes emerged from the interviews: a. Descriptive elements of the project; b. The tablet in the classroom and c. Project evaluation. The analyzes highlight the importance of the role of the teacher and the student. The study considers that the project was important for the students' learning, but the adequate infrastructure for its realization was precarious and needs to be improved and expanded.
Keywords: Public Policy. Tablets in Education. Educational technology. Basic education. Mobile technologies.